PENGUKURAN PERFOMANSI GAME ON LINE DI DAERAH RURAL DALAM VARIASI WAKTU DAN KARAKTER HERO PADA MOBILE LEGEND BANG BANG - Made Sutha Yadnya; Sudi Mariyanto Sasongko; Lalu Alfian Wahyudi (DIELEKTRIKA, 2020)
The use of online games in the Industrial 4.0 eras continues to grow to pamper its consumers. On the consumer side wants to get the best service from providers. This publication is describing the data and connection requirements of online games specifically for Mobile Legend Bam Bang in terms of telecommunications performance. Measurements were made using parameters of throughput, packet loss, and delay. Measurement variations are carried out according to time. The busy time used is 6 am to 11 pm. The results are in accordance with general hypotheses, but there are some things that are anomaly measurements.